Assessing how External Motivation and Preventive Discipline Impact Employee Output in a Supermarket in Bandung - Rani Anggraeni; Senen Machmud; Ester Manik (Majalah Bisnis & IPTEK, 2026)
This research addresses the impact of extrinsic motivation and preventive discipline on employee performance at supermarket in Bandung. The study aims to examine the individual and combined influences of these factors. Using a saturated sampling method, data were collected from 70 employees via questionnaires and analyzed through quantitative techniques, including validity, reliability, and normality tests, along with multiple regression, T tests, and F tests, using SPSS 25. The findings reveal that extrinsic motivation significantly enhances employee performance, while preventive discipline also positively influences it. Both factors collectively impact employee performance. The novelty of this research lies in its examination of how extrinsic motivation and preventive discipline interact within a supermarket context, offering fresh insights into practical strategies for management. By highlighting the connection between motivation and discipline, the study provides a unique approach to enhancing workforce performance. This study emphasizes the need for management to promote motivating strategies and effective disciplinary measures to improve overall employee performance.